"A conceptual four-stage maturity model of a firm's green manufacturing technology alternatives and performance measures". Issue 7 (29th April 2021) - Shukla, Ganesh Prasad; Adil, Gajendra K.
Abstract : Purpose: This paper develops a contingency based model to understand how green technologies and green manufacturing performance measures evolve with the green manufacturing maturity levels of the firms. Design/methodology/approach: A conceptual research model is developed by synthesizing extant literature. An illustrative case study of a paint manufacturing company is conducted, analyzing its five key green initiatives, which it has undertaken to demonstrate the research model. The primary means of data collection was interviews and document analysis. Findings: It was observed that for all the five green initiatives, the choice of green technologies and the use of green manufacturing performance measures corroborate with the proposed research model. Further, the initial green manufacturing effort was motivated to comply with regulations, which subsequently shifted to gain strategic advantage, such as cost reduction and visibility. Research limitations/implications: The proposed model was applied only to an Indian paint manufacturing company with their five key green initiatives, which potentially limits the generalizability of the findings to other industries and/or geographies. Practical implications: The findings would aid practitioners in understanding both selection of green technology and the use of green manufacturing performance measures, based on a firm's maturity stage. Originality/value: This study conducts a much-needed research on the evolution of green technology alternatives and green manufacturing performance measures for firms according to the four-stage maturity model derived from the natural resourced-based view.